Catalytic Asymmetric Three‐component Hydroacyloxylation/ 1, 4‐Conjugate Addition of Ynamides. Issue 13 (9th June 2020) - Li, Xiangqiang; Jiang, Mingyi; Zhan, Tangyu; Cao, Weidi; Feng, Xiaoming
Abstract: A highly enantioselective three‐component hydroacyloxylation/1, 4‐conjugate addition of ortho ‐hydroxybenzyl alcohols, ynamides and carboxylic acids was developed under mild reaction conditions in the presence of a chiral N, N′ ‐dioxide/Sc(OTf)3 complex, which went through in situ generated ortho ‐quinone methides with α‐acyloxyenamides, delivering a range of corresponding chiral α‐acyloxyenamides derivatives containing gem (1, 1)‐diaryl skeletons in moderate to good yields with excellent ee values. The scale‐up experiment and further derivation showed the practicality of this catalytic system. In addition, a possible catalytic cycle and transition state model was proposed to elucidate the origin of the stereoselectivity based on X‐ray crystal structure of the α‐acyloxyenamide intermediate and product. Abstract : A catalytic asymmetric three‐component 1, 4‐conjugate addition of in situ generated ortho ‐quinone methides with α‐acyloxyenamides derived from ynamides and carboxylic acids was achieved under mild reaction conditions by using chiral N, N′ ‐dioxide‐Sc(OTf)3 complex as catalyst, affording a variety of chiral α‐acyloxyenamides derivatives containing gem (1, 1)‐diaryl skeletons in moderate to good yields with excellent enantioselectivities.